Learners’ Perceptions and Attitudes Towards Learning of Calculus in Secondary Schools: The Case of Three Selected Secondary Schools in a District of the Northern Province of Zambia - Collins Chama; Rex L Sampa; Danny Mutambo; Allan Musonda; Felix F. Musonda (Journal of Advanced Research in Education, 2023)
This study sought to examine senior mathematics secondary school learners’ perceptions and attitudes towards the learning of Calculus in a selected district of the Northern Province in Zambia. The research design was Analytical and descriptive. Therefore, quantitative and qualitative data were collected from 400 learners using a questionnaire. The Relative Importance Index (RII) guided the identification and determination of factors influencing learners’ perceptions and attitudes regarding the learning of calculus. The data collected were analyzed using Statistical Package for Social Sciences (SPSS) version 20.0. It was established that the majority of learners perceived calculus to be an important subject as it encouraged them to think deeply thus improving their ability to make daily life decisions. Consequently, learners have a positive perception of calculus and an equally positive attitude towards calculus. Furthermore, it was established that apart from learner effort, parental, peer and teacher support were identified as key drivers in positively influencing students’ learning of Calculus in secondary schools under the study.